Perspectives on contractual relationships and the move to best value in local authorities - Walker, Bruce; Davis, Howard (1999)
This article is concerned with the nature of the contracting relationship in local authorities. After considering some of the implications of a basic model of contracting (principal-agent theory) and questioning some of its implications, we briefly examine whether the Compulsory Competitive Tendering (CCT) regime is likely to have forced many clients and contractors into the more adversarial style of contract management that the theory predicts. We then assess the degree to which parties to local authority contracts act, or wish to act, in a more relational manner and consider some of the implications of the best value regime. We conclude by suggesting that there are some important requirements which need to be placed upon public sector contracting behaviour to limit the implementation of `full' relational styles in practice. - Reproduced
Keywords: Local government